2019
DOI: 10.1186/s13195-019-0503-2
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition and treatment of neuropsychiatric symptoms to improve quality of life in early Alzheimer’s disease: protocol of the BEAT-IT study

Abstract: Background Neuropsychiatric symptoms (NPS) are very common in patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) dementia and are associated with various disadvantageous clinical outcomes including a negative impact on quality of life, caregiver burden, and accelerated disease progression. Despite growing evidence of the efficacy of (non)pharmacological interventions to reduce these symptoms, NPS remain underrecognized and undertreated in memory clinics. The BEhavioural sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 91 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…The pathogenesis of these symptoms is not still completely understood, and the current knowledge supports multifactorial causes, involving the interaction of biological, psychological, and social factors (7). It has been shown that BPSD are associated with high levels of distress both in dementia sufferers and their caregivers, as well as with adverse outcomes, long-term hospitalization, and misuse of medications and increased use of health care resources (8)(9)(10)(11)(12). Thus, in addition to cognitive deterioration, BPSD are a relevant and meaningful clinical target for intervention (13) although are still now considered as non-disease-specific markers (14).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of these symptoms is not still completely understood, and the current knowledge supports multifactorial causes, involving the interaction of biological, psychological, and social factors (7). It has been shown that BPSD are associated with high levels of distress both in dementia sufferers and their caregivers, as well as with adverse outcomes, long-term hospitalization, and misuse of medications and increased use of health care resources (8)(9)(10)(11)(12). Thus, in addition to cognitive deterioration, BPSD are a relevant and meaningful clinical target for intervention (13) although are still now considered as non-disease-specific markers (14).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses about cholinergic system dysfunction [9], Aβ deposits, oxidative stress [10], inflammatory pathways [11], calcium signaling dysfunction [12], hormone imbalance [13], and genetic components [14] have been considered to play important roles in the occurrence and development of AD, although the etiology of this disease is still not precisely known [15]. In addition, although several therapies have been used as compensation for the cholinergic neuronal loss and reduction or prevention of amyloid/tau aggregation and toxicity, such as gene therapy, vaccines, anti-inflammatory agents [16], cholesterol-lowering agents, anti-oxidants [17], and hormone therapy [18] for AD, these single targeted therapies have often been unsuccessful [19,20]. Traditional Chinese Medicine (TCM), with thousands of years of history in China, has received widespread attention, particularly given the few side effects it carries, multi-target treatments, and natural origins [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited via two strategies. A part of the participating physicians were already involved in an intervention study to improve the management of NPS in AD dementia in the memory clinic as part of the BEAT‐IT project 29 . These physicians were interviewed during the first observational wave of the project, in which patients received care as usual and served as a control group (convenience sample).…”
Section: Methodsmentioning
confidence: 99%
“…A part of the participating physicians were already involved in an intervention study to improve the management of NPS in AD dementia in the memory clinic as part of the BEAT-IT project. 29 These physicians were interviewed during the first observational wave of the project, in which patients received care as usual and served as a control group (convenience sample). Furthermore, additional physicians were contacted to ensure maximum variation regarding profession (neurologist/geriatrician), type of hospital where they are employed (general/academic), and years of experience (purposive sampling).…”
Section: Sampling and Recruitmentmentioning
confidence: 99%